The Intermediary Effect of Psychological Capital on the Relationship between Toxic Leadership Behaviors of School Administrators and School Effectiveness - Küçük, Özkan; Demirtaş, Zülfü (Murat TUNCER, 2021)
The purpose of this study is to identify the relationship between toxic (poisonous) leadership, school effectiveness and psychological capital variables with respect to opinions of teachers working in high schools. The population of the study, designed through the descriptive and relational screening model, consists of all the teachers working in secondary schools in the city center of Elazığ during the 2015-2016 academic years. A sample group was not taken from the population, all the teachers in the population were tried to be contacted and data were collected from 808 teachers. According to the study findings, teacher perceptions concerning toxic leadership behaviors of school administrators are at low level for all dimensions; their school effectiveness perceptions are at moderate level and psychological capital perceptions are at moderate level for the optimism dimension, and at high level for the psychological resilience, hope and self-efficacy dimensions. On the other hand, according to findings concerning the intermediary role of psychological capital, psychological capital has an intermediary effect between toxic leadership and school effectiveness.
Keywords: Studies on Education; Eğitim Üzerine Çalışmalar